Implementasi Pengembangan Sistem Media Pembelajaran Pengenalan Komputer: Program Studi Sistem Informasi Universitas PGRI Madiun - Setiawan, Dimas; Arifin, Irsyadul; Ardianto, Rian (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2018)
The development of educational technology is growing rapidly, this is happening with the growing trend in the trend of online learning technology, mobile & multimedia. In the course of logic and program algorithm, students are introduced about the introduction of computer technology, in order to create a technology-based educational environment then made learning media introduction computer, made possible by the learning media, computer introduction, can help the learning process in the course of logic & programming algorithm.